Dinar–Dirham as an Ethical Monetary Framework: Qur’anic Perspectives on Financial Justice in the Digital Economy - Abd Rosyid Rosyid; Aang Kunaifi; Zainol Fata; Fikri Zhilalil Haq (El-Barka Journal of Islamic Economics and Business, 2026)
The contemporary global monetary system based on fiat currency has been associated with various challenges, including inflation, exchange-rate volatility, and monetary instability in several developing economies. This study investigates the concept of money from an Islamic perspective by analyzing Qur’anic references to dinar and dirham as representations of gold- and silver-based monetary instruments. Employing a qualitative approach through thematic Qur’anic interpretation (tafsir maudhu’i) combined with a review of historical and contemporary monetary phenomena, the study examines the relevance of precious metals as measures of value within Islamic economic thought. The analysis focuses primarily on Surah Al-Imran (3:75) and At-Taubah (9:34), alongside historical evidence from selected Muslim-majority countries that have experienced monetary instability under fiat currency regimes. The findings indicate that Qur’anic references to dinar and dirham reflect principles related to value preservation, transactional fairness, and wealth protection. Furthermore, historical observations suggest that gold and silver have exhibited relatively greater long-term stability in purchasing power than several fiat currencies subject to inflationary pressures. This study contributes to the discourse on Islamic monetary economics by offering a reinterpretation of Qur’anic monetary concepts in relation to contemporary debates on monetary stability and alternative currency frameworks in Muslim societies.